Testing of the Structure-Conduct-Performance Hypothesis for Industrial Banking Profitability: Evidence from Indonesia - Asngari, Imam (Integrated Journal of Business and Economics (IJBE), 2024)
This study aims to test the validity of the Structure Conduct and Performance (SCP) hypothesis on banking profitability in Indonesia. This research data comes from banking financial statements from the Financial Services Authority (OJK) and Bank Indonesia. The analysis method uses the panel data regression method. The banking industry studied includes 110 conventional commercial banks and Islamic banks from 2010-2019. This research has found that the profitability performance of the banking industry is statistically significantly influenced by concentration, market share, cost efficiency to generate revenue, bank size, net interest income margin, Bank Indonesia's benchmark interest rate, and economic growth. Meanwhile, inflation is insignificant. The contribution of the research was to develop of Structure Conduct Performance (SCP) theory. The SCP is applicable to Indonesian banking and it is the Hybrid of the Efficient-Structure Traditional Hypothesis which states that the effects of efficiency and market concentration have improved banking profitability performance. The combination of structure, market share, and efficiency supports the hypotheses on Efficiency and SCP Traditional. High banking profitability due to the combination of efficiency and market concentration formed by increased assets and mergers. Therefore, OJK and Bank Indonesia in encouraging asset improvement through future mergers can improve efficiency, the competitiveness of the banking industry, the and economic stability of Indonesia.